2004
DOI: 10.1111/j.1471-4159.2004.02526.x
|View full text |Cite
|
Sign up to set email alerts
|

AMPA protects cultured neurons against glutamate excitotoxicity through a phosphatidylinositol 3‐kinase‐dependent activation in extracellular signal‐regulated kinase to upregulate BDNF gene expression

Abstract: The signal transduction and molecular mechanisms underlying a-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA)-mediated neuroprotection are unknown. In the present study, we determined a major AMPA receptor-mediated neuroprotective pathway. Exposure of cerebellar granule cells to AMPA (500 lM) + aniracetam (1 lM), a known blocker of AMPA receptor desensitization, evoked an accumulation of brain-derived neurotropic factor (BDNF) in the culture medium and enhanced TrkB-tyrosine phosphorylation following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 58 publications
(76 reference statements)
7
62
1
1
Order By: Relevance
“…Increased AMPA receptor 'throughput' may ultimately cause downstream neuroproliferative effects through the induction of brain-derived neurotrophic factor and multiple intracellular signaling cascades (Lauterborn et al, 2000;Lauterborn et al, 2009;Mackowiak et al, 2002;Voss et al, 2007;Wu et al, 2004;Zhang et al, 2009). These speculations accord with previous evidence .…”
Section: Association With Clinical Responsesupporting
confidence: 81%
“…Increased AMPA receptor 'throughput' may ultimately cause downstream neuroproliferative effects through the induction of brain-derived neurotrophic factor and multiple intracellular signaling cascades (Lauterborn et al, 2000;Lauterborn et al, 2009;Mackowiak et al, 2002;Voss et al, 2007;Wu et al, 2004;Zhang et al, 2009). These speculations accord with previous evidence .…”
Section: Association With Clinical Responsesupporting
confidence: 81%
“…It was previously found that AMPA at a high concentration (500 μM) increased granule cells survival (Wu et al, 2004). Our data support these findings but also show that much lower concentrations of either AMPA or kainate are required for this action and that AMPA or NMDA receptors can independently mediate the increased survival of cerebellar granule neurons.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, it has been suggested that ERK I/II plays an essential role in the neuroprotective processes (Wu et al, 2004;Shen et al, 2009;Jiang et al, 2009). Our study present evidence for the first time that ERK I/II activation by taurine may be an important step for the neuroprotection exerted by taurine.…”
Section: Discussionsupporting
confidence: 53%